2017
DOI: 10.5603/kp.a2016.0110
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency is associated with coronary artery tortuosity

Abstract: A b s t r a c tBackground: Increasing evidence suggests a relationship between vitamin D (VD) insufficiency and cardiovascular disease. Aim:We aimed to investigate the association between serum 25-hydroxyvitamin D (25-OH VD) with coronary tortuosity (CT) in patients with normal or near-normal (< 40% stenosis) coronary arteries. Methods:The present study was cross-sectional and observational. We enrolled 356 consecutive patients who had undergone coronary angiography for suspected ischaemic heart disease and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Several studies have been performed on the association between vitamin D status and different aspects of cardiovascular disorders, including metabolic syndrome,9 hypertension,10,11 calcified atherosclerotic plaques,12,13 severity of luminal stenosis in coronary arteries,14,15 tortuosity of coronary arteries,16 and even the final outcomes or lethal events of coronary artery disease (CAD) 17. In this regard, the need for increased attention has been proposed, suggesting the role of vitamin D deficiency as a risk factor for CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been performed on the association between vitamin D status and different aspects of cardiovascular disorders, including metabolic syndrome,9 hypertension,10,11 calcified atherosclerotic plaques,12,13 severity of luminal stenosis in coronary arteries,14,15 tortuosity of coronary arteries,16 and even the final outcomes or lethal events of coronary artery disease (CAD) 17. In this regard, the need for increased attention has been proposed, suggesting the role of vitamin D deficiency as a risk factor for CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Some trials showed connection between 25(OH)D serum level and blood pressure (BP), and some didn't. Moreover, other trials showed that vitamin D levels are associated with development and course of not only HTN but also other CVDs including coronary heart disease and heart failure [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%